Optimal Couples of Rearrangement Invariant Spaces for Generalized Maximal Operators - Irshaad Ahmed; Waqas Nazeer (Journal of Function Spaces)
The optimal couples of rearrangement invariant spaces for boundedness of a generalized maximal operator, associated with a quasiconcave function, have been characterized in terms of certain indices connected with rearrangement invariant spaces and quasiconcave functions.